If we evaluate the function at infinity, we get:
![\large\displaystyle\text{$\begin{gathered}\sf \bf{\displaystyle L = \lim_(x \to \infty){ (√(4x^4 + x^2 + 1))/(x^2 + 1) } = (\infty)/(\infty) } \end{gathered}$}](https://img.qammunity.org/2023/formulas/mathematics/high-school/p3owflct7tggmaxj4akzk1gcla1fk8b8td.png)
Therefore, being an indeterminate form, we must multiply and divide by the highest degree monomial (x²; remember that we divide the powers of the numerator by 2 since they are inside a square root):
![\begin{align*}L &= \lim_(x \to \infty){ (√(4x^4 + x^2 + 1))/(x^2 + 1) \cdot ((1)/(x^2))/((1)/(x^2))}\\ & = \lim_(x \to \infty){\frac{ \sqrt{4 + (1)/(x^2) + (1)/(x^4)} }{1 + (1)/(x^2)}} \end{align*}](https://img.qammunity.org/2023/formulas/mathematics/high-school/a80xfep9oyh5g8w9zftc4fy2lg9av62dwx.png)
![\large\displaystyle\text{$\begin{gathered}\sf \bf{L= \lim_(x \to \infty)\frac{\sqrt{4x^2+x^(2) +1 } }{x^2+1}\cdot((1)/(x^(2) ) )/((1)/(x^(2) ) ) } \end{gathered}$}\\\large\displaystyle\text{$\begin{gathered}\sf \bf{ \ \ \ = \lim_(x \to \infty) \frac{\sqrt{4+(1)/(x^(2) )+(1)/(x^(4) ) } }{1+(1)/(x^(2) ) } } \end{gathered}$}](https://img.qammunity.org/2023/formulas/mathematics/high-school/wl2kriptui1tedjc7ttte5o88la08bxqrd.png)
Then, evaluated at infinity, we have:
![\large\displaystyle\text{$\begin{gathered}\sf \bf{\displaystyle L = (√(4 + 0 + 0))/(1 + 0) = (√(4))/(1) = 2} \end{gathered}$}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2rgnc8ludqg9obaarptgqiidfhngbkcogf.png)
So the limit is 2.